Back Channeling Speech Style Used by Colleen Mcguire as the Main Character of the Novel Savage Land - Retno Budi Astuti (Jurnal Sinestesia, 2019)
This research discusses about one of the speech styles of feminine gender while having a conversation, which is back channeling. The data used to be analyzed in this research is taken from the dialogues and the narration of the main character named Colleen McGuire in the novel Savage Land written by Janet Dailey. Qualitative method was used in doing this research because the data are presented in the form of written words or verbal expressions. The result of this research shows that Collen McGuire as the main character of the novel Savage Land used back channeling in her dialogues and narration. Out of 31 data, it shows that there are 16 data where she uses “nodding” gesture, 9 data where she uses the word “yes”, 3 data where she uses the word “all right”, 1 data where she uses the word “okay”, 1 data where she uses the word “right”, and 1 data where she uses the word “right away”.